The relationship between self-care behavior and the quality of life of coronary heart disease sufferers in the Heart Clinic of Kendari General Hospital - La Sulu, La Sulu; Razak, Muslimin Haji (Program Studi Keperawatan, Politeknik Negeri Subang, 2024)
Background: Coronary heart disease (CHD) can lead to declines in both physical and psychological functioning, affecting self-care behavior and quality of life. Understanding the relationship between these two factors is critical for improving patient outcomes. Purpose: This study aimed to explore the relationship between self-care behavior and quality of life in patients with CHD at the Heart Clinic of Kendari General Hospital. Methods: A quantitative cross-sectional study was conducted with 61 respondents selected through purposive sampling. The study used self-care behavior questionnaires (SCCHDI) and quality of life assessments (SF-26). Data were analyzed using the Spearman correlation test to determine the relationship between self-care behavior and quality of life. Results: The Spearman correlation analysis revealed a significant relationship between self-care behavior and quality of life in CHD patients, with a p-value of 0.001. This suggests that improved self-care behaviors are associated with better quality of life outcomes. Conclusion: The findings underscore the importance of promoting self-care behavior in patients with coronary heart disease to enhance their quality of life. Healthcare providers, especially nurses, should take an active role in providing education and motivation to encourage effective self-care practices, ultimately improving patient well-being.